Fetal Brain-Sparing, Postnatal Cerebral Oxygenation, and Neurodevelopment at 4 Years of Age Following Fetal Growth Restriction - Richter, Anne E.; Salavati, Sahar; Kooi, Elisabeth M. W.; Heijer, Anne E. den; Foreman, Anne B.; Schoots, Mirthe H.; Bilardo, Caterina M.; Scherjon, Sicco A.; Tanis, Jozien C.; Bos, Arend F. (Frontiers in Pediatrics, 2020)
Objectives: To assess the role of fetal brain-sparing and postnatal cerebral oxygen saturation (rcSO2) as determinants of long-term neurodevelopmental outcome following fetal growth restriction (FGR). Methods: This was a prospective follow-up study of an FGR cohort of 41 children. Prenatally, the presence of fetal brain-sparing (cerebroplacental ratio < 1) was assessed by Doppler ultrasound. During the first two days after birth, rcSO2 was measured with near-infrared spectroscopy. At 4 years of age, intelligence (IQ points), behavior (T-scores), and executive function (T-scores) were assessed using the Wechsler Preschool and Primary Scale of Intelligence, Child Behavior Checklist, and Behavior Rating Inventory of Executive Function—Preschool Version, respectively. Using linear regression analyses, we tested the association (p < 0.05) between brain-sparing/rcSO2 and normed neurodevelopmental scores. Results: Twenty-six children (gestational age ranging from 28.0 to 39.9 weeks) participated in the follow-up at a median age of 4.3 (range: 3.6 to 4.4) years. Autism spectrum disorder was reported in three children (11.5%). Fetal brain-sparing was associated with better total and externalizing behavior (betas: −0.519 and −0.494, respectively). RcSO2 levels above the lowest quartile, particularly on postnatal day 2 (≥ 77%), were associated with better total and internalizing behavior and executive functioning (betas: −0.582, −0.489, and −0.467, respectively), but also lower performance IQ (beta: −0.530). Brain-sparing mediated some but not all of these associations. Conclusions: In this FGR cohort, fetal brain-sparing and high postnatal rcSO2 were—independently, but also as a reflection of the same mechanism—associated with better behavior and executive function. Postnatal cerebral hyperoxia, however, was negatively associated with brain functions responsible for performance IQ.